Maternal Stress and Human Milk Antibodies During the COVID-19 Pandemic - Juncker, Hannah G.; Ruhé, Eliza J. M.; Korosi, Aniko; van Goudoever, Johannes B.; van Gils, Marit J.; van Keulen, Britt J. (Frontiers in Nutrition, 2022)
Importance: SARS-CoV-2-specific antibodies in human milk might protect the breastfed infant against COVID-19. One of the factors that may influence human milk antibodies is psychological stress, which is suggested to be increased in lactating women during the COVID-19 pandemic. Objective: To determine whether psychological stress is increased in lactating women during the COVID-19 pandemic, and if maternal stress is associated with the level of SARS-CoV-2-specific antibodies in human milk. Design: Population-based prospective cohort study. Setting: Data collection took place in the Netherlands between October 2020 and February 2021. Participants: Lactating women living in the Netherlands were eligible to participate in this study. In total, 2310 women were included in the study. Exposures: Stress exposure during the COVID-19 pandemic was determined using the Perceived Stress Scale (PSS) questionnaire and maternal lifetime stress was determined by the Life Stressor Checklist – revised (LSC-r) questionnaire. Main Outcome(s) and Measure(s): Stress experience during the COVID-19 pandemic was compared with a pre-pandemic cohort. SARS-CoV-2-specific antibodies in human milk were measured using an Enzyme-Linked Immunosorbent Assay (ELISA) with the Spike protein of SARS-CoV-2. The association between stress and human milk antibodies was determined using a multiple regression model. Results: The PSS score of lactating mothers was not increased during the pandemic. Six hundred ninety-one participants had SARS-CoV-2-specific antibodies and were included in the regression models to assess the association between stress and human milk antibodies. No association was found between PSS scores and human milk antibodies. In contrast, the LSC-r score was negatively associated with SARS-CoV-2-specific IgA in human milk (β = 0.98, 95% CI: 0.96 - 0.997, p=0.03) Conclusions and Relevance: Our results suggest that lactating women in the Netherlands did not experience higher perceived stress levels during the COVID-19 pandemic. Breastfed infants of mothers with high chronic stress levels receive lower amounts of antibodies through human milk, which possibly makes them more vulnerable to respiratory infections. This emphasizes the importance of psychological wellbeing during lactation.